The Role of Literature in Teaching Critical Reading - Kurnia Ningsih (International Conference on Languages and Arts, 2012)
Being an academic community, especially in tertiary level (college and Universities) students should have higher level of thinking. This level can be reached through critical reading that offers opportunities for students actively to comprehend, make inferences, consider ideas, learn to evaluate and give arguments toward what the text says. To develop critical reading does not simply deal with the strategy of teaching reading, but also the choice of materials. Literature (literary work) as a material for reading offers the chance to build critical reading and thinking skills since the text are creative and imaginative work. It deals with phenomena occures in daily life. The text is able to invite the readers to think creatively, read between the lines, as well as develop their imagination. It activates the cognitive and affective factors required by intellectual community. Thus this paper focuses on the role of literature in teaching critical reading that should be developed from the beginning.